Overexpression of Lifeact-GFP Disrupts F-Actin Organization in Cardiomyocytes and Impairs Cardiac Function - Xu, Rui; Du, Shaojun (Frontiers in Cell and Developmental Biology, 2021)
Lifeact-GFP is a frequently used molecular probe to study F-actin structure and dynamic assembly in living cells. In this study, we generated transgenic zebrafish models expressing Lifeact-GFP specifically in cardiac muscles to investigate the effect of Lifeact-GFP on heart development and its application to study cardiomyopathy. The data showed that transgenic zebrafish with low to moderate levels of Lifeact-GFP expression could be used as a good model to study contractile dynamics of actin filaments in cardiac muscles in vivo. Using this model, we demonstrated that loss of Smyd1b, a lysine methyltransferase, disrupted F-actin filament organization in cardiomyocytes of zebrafish embryos. Our studies, however, also demonstrated that strong Lifeact-GFP expression in cardiomyocytes was detrimental to actin filament organization in cardiomyocytes that led to pericardial edema and early embryonic lethality of zebrafish embryos. Collectively, these data suggest that although Lifeact-GFP is a good probe for visualizing F-actin dynamics, transgenic models need to be carefully evaluated to avoid artifacts induced by Lifeact-GFP overexpression.